2016
DOI: 10.1259/bjr.20150775
|View full text |Cite
|
Sign up to set email alerts
|

A diffusion-based quantification technique for assessment of sacroiliitis in adolescents with enthesitis-related arthritis

Abstract: Objective:To investigate the use of a quantitative diffusion-weighted imaging (DWI) tool for measuring inflammation of the sacroiliac joints (SIJs) in enthesitis-related arthritis (ERA).Methods:A retrospective study was performed with institutional review board approval. Subjects were adolescents who had undergone MRI of the SIJs since January 2010. 10 patients with a clinical diagnosis of ERA and 10 controls with a clinical diagnosis of mechanical back pain were assessed. Axial T1 weighted, short tau inversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 24 publications
(35 reference statements)
2
31
0
1
Order By: Relevance
“…79 These are typically increased in the affected tissues. 80 The relevance of DWI for inflammatory rheumatic diseases is well demonstrated by the numerous studies promoting the application of ADC as a biomarker. For instance, Barendregt et al, analyzing the synovium, demonstrated that ADC values discriminate between active and inactive JIA.…”
Section: Diffusion-weighted Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…79 These are typically increased in the affected tissues. 80 The relevance of DWI for inflammatory rheumatic diseases is well demonstrated by the numerous studies promoting the application of ADC as a biomarker. For instance, Barendregt et al, analyzing the synovium, demonstrated that ADC values discriminate between active and inactive JIA.…”
Section: Diffusion-weighted Imagingmentioning
confidence: 99%
“…81 Similarly, Vendhan et al successfully used DWI for sacroiliitis in patients with enthesitis-related arthritis, although this group of researchers, aiming to reduce the effect of factors that could hamper the reproducibility of the diffusion-based measurements (e.g., bvalues, gradient nonlinearities), proposed a normalization of the data. 80 The ratio between the ADC values extracted from ROIs in the sacroiliac joint (i.e., including joint space, synovium, and subchondral bone) and those collected from ROIs in the healthy sacral bone, provides an internal reference standard reducing the effect of confounding factors. 80 The same approach was successfully applied to evaluate the treatment response in children with the same disease, demonstrating that ADC and normalized ADC measurements were good predictors of the radiologic response (AUC ADC :0.97, AUC nADC :0.82) and moderate predictors of the clinical response (AUC ADC :0.67, AUC nADC :0.78).…”
Section: Diffusion-weighted Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In juvenile idiopathic arthritis (JIA), research into DWI had been conducted in the knee joint [44][45][46][47] and the sacroiliac (SI) joints. 48,49 In the SI joints of patients with enthesis-related arthritis, normalized ADC values (calculated as ADC of the linear ROI over SI joints/by ADC of reference ROI in normal sacral bone) were significantly higher (2.57) than in controls with mechanical lower back pain (1.28). 49 In a further study from this group, a similar patient group was imaged using DWI with the same ROI approach before and after start of anti-TNF treatment and results show that the difference in ADC values and normalized ADC values before and after treatment initiation was larger in radiological responders as compared with radiological non-responders.…”
Section: Dwi In Juvenile Idiopathic Arthritismentioning
confidence: 99%
“…48,49 In the SI joints of patients with enthesis-related arthritis, normalized ADC values (calculated as ADC of the linear ROI over SI joints/by ADC of reference ROI in normal sacral bone) were significantly higher (2.57) than in controls with mechanical lower back pain (1.28). 49 In a further study from this group, a similar patient group was imaged using DWI with the same ROI approach before and after start of anti-TNF treatment and results show that the difference in ADC values and normalized ADC values before and after treatment initiation was larger in radiological responders as compared with radiological non-responders. 48 Starting in 2012, feasibility of DWI for the imaging of synovium in the pediatric joints was studied and both Neubauer et al and Barendregt et al demonstrated that imaging of synovial tissue of the knee was possible and that differentiation between synovium and joint fluid can be made.…”
Section: Dwi In Juvenile Idiopathic Arthritismentioning
confidence: 99%